Human Resource Practices for Service Excellence in the Hospitality Industry: A Systematic Literature Review - Jaya Purnama; Anita (SM Institute, 2026)
This systematic literature review synthesizes evidence on Human Resource Practices (HRPs) that support service excellence in the hospitality industry. The review organizes the source manuscript's evidence set of 20 retained studies through a PRISMA 2020-informed identification, screening, eligibility, and inclusion logic, followed by thematic synthesis using open, axial, and selective coding. The findings identify eight broad HR practice domains: recruitment and selection, training and development, performance management, leadership, employee empowerment, high-performance human resource practices, sustainable human resource management, and human capital development. Across the literature, psychological empowerment, employee engagement, job satisfaction, organizational commitment, service climate, and service-oriented behavior function as employee-related mechanisms linking HR systems with service outcomes. Service quality and service performance emerge as the most immediate outcomes, while customer satisfaction, organizational performance, and competitive advantage represent downstream consequences. The synthesis indicates that service excellence is more plausibly explained by an integrated HR architecture than by isolated practices. The review proposes a multistage pathway connecting HR practices, employee experience, service behavior, service excellence, and customer and organizational value. These findings position HRM as a service-enabling capability in hospitality organizations.